2007
DOI: 10.1161/hypertensionaha.106.085704
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Endothelial Nitric Oxide Synthase in Vascular Effects of Erythropoietin

Abstract: Abstract-Erythropoietin (EPO) fosters tissue oxygenation by stimulating erythropoiesis. More recently, EPO has been recognized as a tissue-protective cytokine.In this study, we tested the hypothesis that endothelial NO synthase (eNOS) plays a key role in the vascular protective effect of EPO. A murine model of wire-induced injury of carotid artery was used to examine the effect of EPO on endothelial repair and arterial wall architecture. Recombinant human EPO (1000 U/kg, SC, biweekly) was administered for 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 42 publications
4
73
0
1
Order By: Relevance
“…Also EPO has anti-apoptotic, antiinflammatory, and antioxidative activities. EPO receptor was detected in some tissues such as brain, heart, lung, liver, kidney, and vascular endothelium (Brines & Cerami, 2006;d'Uscio et al, 2007;Heeschen et al, 2003;Sharples & Yaqoob, 2006;Wu et al, 2010b). EPO may prevent the hemorrhagic shock-induced organ damage in rats by decreasing the production of pro-inflammatory cytokines (Wu et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also EPO has anti-apoptotic, antiinflammatory, and antioxidative activities. EPO receptor was detected in some tissues such as brain, heart, lung, liver, kidney, and vascular endothelium (Brines & Cerami, 2006;d'Uscio et al, 2007;Heeschen et al, 2003;Sharples & Yaqoob, 2006;Wu et al, 2010b). EPO may prevent the hemorrhagic shock-induced organ damage in rats by decreasing the production of pro-inflammatory cytokines (Wu et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide plays a major role in the pathogenesis of sepsis (Santos et al, 2012) and EPO inhibits the activity of nitric oxide synthase (d'Uscio et al, 2007) which is responsible for the synthesis of nitric oxide. Wu et al (2010b) reported that pre-treatment with low dose (300 U/kg) EPO suppresses the release of TNF-a and IL-6 production, decreases organ damage, and improves survival rate after hemorrhagic shock in conscious rats.…”
mentioning
confidence: 99%
“…Male C57BL/6J (wild-type) and eNOS-deficient mice (C57BL/6J-Nos3 tm1Unc ) (Jackson Laboratory, Bar Harbor, ME) were distributed into two groups: no treatment (n = 6 mice) and EPO treatment (n = 6 mice, recombinant human EPO 1000 U/kg body weight subcutaneous, bi-weekly, Amgen Thousand Oaks, CA) [10,12]. After 14 days, mice were anesthetized and euthanized by an intraperitoneal injection of pentobarbital (Nembutal Sodium, 60 mg/kg body weight).…”
Section: Methodsmentioning
confidence: 99%
“…The profile of blood cells in wild type and eNOS-deficient mice treated with EPO were performed with ABAXIS VetScan HMII Hematology System (Union City, CA), as reported in our previous study [10].…”
Section: Methodsmentioning
confidence: 99%
“…Human recombinant EPO (100 or 1000 IU/kg) (Chugai, Tokyo) (13,14) or PBS was injected intraperitoneally three times per week, that is, at 0, 3,6,9,12,15,18,21,24, and 27 days after surgery. There were six animals in each group.…”
Section: Experimental Protocolsmentioning
confidence: 99%